2019
DOI: 10.1021/acssuschemeng.8b05727
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Separable Nanospherical g-C3N4@Fe3O4 as a Recyclable Material for Chromium Adsorption and Visible-Light-Driven Catalytic Reduction of Aromatic Nitro Compounds

Abstract: Graphite-like graphitic carbon nitride (g-C 3 N 4 ) has gained considerable interest in the past few years. However, merely a few studies have been undertaken regarding the application of g-C 3 N 4 for metal adsorption and visible-lightdriven reduction of aromatic nitro compounds. Here, we describe a versatile method for the preparation of g-C 3 N 4 nanocomposite decorated with magnetite nanoparticles (g-C 3 N 4 @Fe 3 O 4 NPs) that subsequently showed their efficiency in sequestration of Cr(VI)/Cr(III) and NaB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 58 publications
1
65
0
Order By: Relevance
“…So the combination of adsorption with photocatalysis should fabricate a class of materials with higher efficiency. Many reports have been devoted to the development of the heterojunction photocatalysts based on g-C 3 N 4 with the synergetic effect of adsorption and photocatalytic degradation capability [44][45][46][47][48]. The construction of these heterojunction boosted the separation efficiency of photoinduced carriers under visible-light illumination and enhanced the adsorption capability.…”
Section: Introductionmentioning
confidence: 99%
“…So the combination of adsorption with photocatalysis should fabricate a class of materials with higher efficiency. Many reports have been devoted to the development of the heterojunction photocatalysts based on g-C 3 N 4 with the synergetic effect of adsorption and photocatalytic degradation capability [44][45][46][47][48]. The construction of these heterojunction boosted the separation efficiency of photoinduced carriers under visible-light illumination and enhanced the adsorption capability.…”
Section: Introductionmentioning
confidence: 99%
“…After that, 2, 2′‐bipyridyl (2 equiv., 25.24 mg) was added to the resultant solution and stirred at room temperature. The resulting, yellow‐colored precipitation was produced by adding excess amounts of diethyl ether (19,33,34). The final product was filtered at room temperature and dried.…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Edrisi et al synthesized g-C 3 N 4 94 according to the reported method. 61 g-C 3 N 4 94 was functionalized with Fe 3 O 4 nanoparticles 62 to give Fe 3 O 4 @g-C 3 N 4 95. Finally, Fe 3 O 4 @g-C 3 N 4 –SO 3 H 96 was washed with methanol and ethyl acetate and afterward dried under vacuum at 60 °C ( Scheme 34 ).…”
Section: The Synthesis Of Pyridine Derivatives By Diverse Magnetic Ca...mentioning
confidence: 99%